Combination ecosystem green engineering and early life history processes to enhance the intertidal biodiversity in the Port of East London - Mafanya, Sandisiwer (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science, 2020)
Marine coastal ecosystems are highly impacted by anthropogenic activities, including the development of, and practices within, harbours and/or ports. Artificial structures associated with harbours have a different chemical composition, texture and orientation than that of the natural benthic habitats they have replaced, and are therefore not generally favourable for the settlement and occurrence of indigenous species. Attempts are being made to identify what structures and materials can be used to aid in the rehabilitation of native species within harbours. The aim of this study was to investigate the effects of utilising environmentally-friendly artificial structures (tiles) with varying complexity (crevices and ridges with different depths) with ecological engineers (the indigenous bivalve Perna perna), on the associated benthic biodiversity within an international port in South Africa (Port of East London). The objectives of the study were to test the effects of artificial habitat complexity and the presence of bivalves on 1) the growth, mortality and biomass of a selected model species of ecosystem engineer (P. perna), and 2) the associated intertidal biodiversity. Tiles seeded with bivalves (P. perna) were deployed at two sites in the Port of East London and monitored monthly over a period of 12 months (November 2016-October 2017) to assess survival, growth and associated biodiversity. Environmental variables were also measured every month. The results of the three-way repeated measures ANOVAs indicated that tile treatment (especially high complexity of 2.5 and 5 cm) had an effect on the diversity of mobile species, length, height and biomass of the bivalves used as model ecosystem engineer, indicating the potentials for protection from wave dislodgement and refuge provision. Treatment (especially flat tiles) also had an effect on sessile/sedentary species diversity, indicating the greater proportion of space provided by these non-complex tiles. In addition, month had an effect on the mortality, height and biomass of the bivalves. Mortality was highest in October 2017, while the growth in height and biomass of P. perna were largest in January and October 2017 respectively. The use of artificial tiles also had a positive effect on the survival, growth, and biomass of bivalves (especially the length, weight and dry weight in 2.5 cm and 5 cm complexity). Additionally, this research investigated patterns of settlement and recruitment of the local bivalve population (P. perna) in the Port of East London and adjacent natural coastline to understand the early life history temporal and spatial dynamics of this model ecosystem engineer species. Settlement and recruitment were assessed every month by deploying and replacing artificial collectors for a total period of 19 months (November 2016-May 2018). The results of the two-way ANOVAs indicated that month and site (port vs natural) had an effect on settlement and recruitment of bivalves. Settlement and recruitment of bivalves were highest in July 2017 (port) and March 2018 (natural rocky shore). This study has highlighted that the use of artificial concrete tiles with increased complexity, as well as the investigation of the early stages of mussel populations could be important to consider in a framework of rehabilitation of urban coastal environments such as the Port of East London. Ecological engineering (in terms of increased complexity and heterogeneity) has indeed the potentials to be incorporated in South African programmes aiming at improving natural biodiversity in coastal urban environments. Nonetheless, the spatio-temporal variability of early driver of mussel populations (settlement and recruitment) is also an important feature to be closely monitored if biodiversity in South African coastal armouring is to be enhanced effectively and in the long term.
Keywords: Biotic communities -- South Africa -- East London; Perna -- Ecology --South Africa -- South Africa-- East London; Mexilhao mussel -- Ecology -- South Africa -- East London; Habitat (Ecology) -- Modification -- South Africa -- East London; Benthic animals -- Effect of habitat modification on -- South Africa -- East London; Harbors -- Environmental aspects -- South Africa -- East London